The enigma of anger : - Keizer, Garret (Jossey-Bass, 2002)
The book is deeply Christian, suffused with images of crucifixion, Holy Eucharist and the Sermon on the Mount but it is hardly parochial, and practitioners of other faiths will find capacious truths in Keizer's perfectly particular reflections. The book is distinguished, above all, by its prose. What might have been merely a spiritual "how-to" on anger management is transformed into a literary achievement by Keizer's way with words, from the opening description of a sugar maple tree to the concluding ode to Samuel Johnson.